Using Moringa (Moringa oleifera Lamm) in Concentrate Feed to Improve Body Weight, Scrotal Circumference, and Semen Production of Kacang Goat - Rokana, Efi; Suyadi, Suyadi; Peasetyo, Endry Nugroho; Isdiantoni, Isdiantoni (Universitas Halu Oleo, 2023)
ABSTRACT This study aims to determine the effect of Moringa leaf powder (Moringa oleifera Lamm) on concentrated feedstuff to improve the body weight, scrotal circumference, and semen production of kacang goat. A total of 20 male kacang goats aged 12-18 months with an average body weight of 15.96±1.82 kg have been used in this study. The feedstuff given is elephant grass (Pennisetum purpureum) as basal feed and concentrated feed substituted with Moringa leaf powder in isoprotein feed. This study uses a completely randomized design. The male kacang goats are divided into 4 treatment groups with different dose of Moringa leaf powder substitution in the concentrated feed, namely P0 = 0%, P1 = 10%, P2 = 20%, and P3 = 30%. Each treatment is repeated five times. The data are then analyzed by ANOVA. Analysis of the nutritional content of Moringa leaf powder substituted in concentrate feed includes DM content = 87. 98%; OM = 91.59%; CFb = 8.03%; CP = 27.73%; CF = 4.16%; NFE = 39.92%; ADF = 8.68%; NDF = 9.96%; Tannin = 29.64%; Saponin = 2.37%, GE = 3997.00 cal / g. The results show that substituting Moringa leaf powder in concentrated feed has a significantly different effect (P 0.05) on the amount of feed consumption and semen production. The study concludes that feeding with Moringa leaf powder by 20% as concentrate substitution is given 1% of body weight (based on Dry Matter) can be applied to increase body weight, scrotal circumference, and semen production of male kacang goats. Keywords: kacang goat, Moringa (Moringa oleifera Lamm), scrotal circumference, semen production, substitution.